How to resolve the enigma of diurnal malate remobilisation from the vacuole in plants with crassulacean acid metabolism?. Issue 6 (30th December 2020) - Ceusters, Nathalie; Borland, Anne M.; Ceusters, Johan
Summary: Opening of stomata in plants with crassulacean acid metabolism (CAM) is mainly shifted to the night period when atmospheric CO2 is fixed by phosphoenolpyruvate carboxylase and stored as malic acid in the vacuole. As such, CAM plants ameliorate transpirational water losses and display substantially higher water‐use efficiency compared with C3 and C4 plants. In the past decade significant technical advances have allowed an unprecedented exploration of genomes, transcriptomes, proteomes and metabolomes of CAM plants and efforts are ongoing to engineer the CAM pathway in C3 plants. Whilst research efforts have traditionally focused on nocturnal carboxylation, less information is known regarding the drivers behind diurnal malate remobilisation from the vacuole that liberates CO2 to be fixed by RuBisCo behind closed stomata. To shed more light on this process, we provide a stoichiometric analysis to identify potentially rate‐limiting steps underpinning diurnal malate mobilisation and help direct future research efforts. Within this remit we address three key questions: Q1 Does light‐dependent assimilation of CO2 via RuBisCo dictate the rate of malate mobilisation? Q2: Do the enzymes responsible for malate decarboxylation limit daytime mobilisation from the vacuole? Q3: Does malate efflux from the vacuole set the pace of decarboxylation?